The Potential Use of Anthocyanin in Butterfly Pea (Clinoteria ternatea) Petals as Colorimetric Indicator in Intelligent Food Packaging Article - Omar, Siti Radhiah; NOH, AHMAD ADHAM; ROHAIZAN, AHMAD NAIM (Malaysian Journal of Science Health & Technology, 2022)
Butterfly pea is a perennial leguminous twiner that lives within the tropical belt and certain warm areas. Butterfly pea contains anthocyanin that are highly sensitive towards any change of pH, making them suitable to be used as pH indicator. The mechanism of the pH sensing capabilities of anthocyanin from butterfly pea involves four reversible structure of anthocyanin that are present in different range of pH: flavylium cation, hemiketal, quinonoid base and chalcone. Colorimetric indicator is a tool that are used in an intelligent food packaging. Its purpose in intelligent food packaging is to provide information of the food contained inside through colour changes that are visible to naked eyes. This colorimetric indicator utilizes pH indicator to assess the freshness of the food by measuring the change of pH that the product undergoes. Anthocyanin from butterfly pea provides an option of natural and organic pH indicator as opposes to synthetic pH indicators that can cause health issues. Anthocyanin from butterfly pea is capable to react towards any change of pH both acidic and basic, stable at least up to 60 days and are organic, perfect to be used in intelligent food packaging and other food related purposes.